ANALISIS KESULITAN BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DIKELAS III SD NEGERI MANNURUKI - Nur Arliani.M; Muhajir; Try Gustaf Said (STKIP Subang, 2026)
This study aims to analyze the factors causing learning difficulties among students in the Pancasila education subject in the third grade of SD Negeri Mannuruki, Makassar. The research method used is descriptive qualitative with data collection techniques through direct observation and in-depth interviews with teachers and students. The results of the study show that students' learning difficulties are not singular but rather an accumulation of internal and external factors. Cognitively, students experience difficulties in understanding abstract terms in Pancasila. Meanwhile, behaviorally, there is a tendency for students to evade tasks through 'stubborn' attitudes or lack of focus due to an inability to understand instructions. The dominant internal factors include low concentration, abstract material that is far from the children's reality, and emotional health issues in the form of feelings of inferiority. The external factors are triggered by a lack of learning support at home due to the busyness of parents and the influence of uncontrolled gadget use. The findings of this study indicate a negative correlation between student behavior and academic achievement, where a lack of focus directly hinders optimal material absorption